2019
DOI: 10.48550/arxiv.1912.00471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maximal Likely Phase Lines for a Reduced Ice Growth Model

Abstract: We study the impact of Brownian noise on transitions between metastable equilibrium states in a stochastic ice sheet model. Two methods to accomplish different objectives are employed. The maximal likely trajectory by maximizing the probability density function and numerically solving the Fokker-Planck equation shows how the system will evolve over time. We have especially studied the maximal likely trajectories starting near the ice-free metastable state, and examined whether they evolve to or near the ice-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Subsequently, Zheng et al [38] developed a probabilistic framework to investigate the maximum likelihood climate change for an energy balance system under the combined influence of greenhouse effect and α-stable Lévy motions. Additionally, there are also some researchers using the Lévy motion to characterize the random fluctuations emerged in neural systems [28], gene networks [6], epidemic model [21], and the Earth systems [2,20,33,34,37].…”
Section: Mathematics Subject Classification (2020) Msc 60g51 • Msc 60...mentioning
confidence: 99%
“…Subsequently, Zheng et al [38] developed a probabilistic framework to investigate the maximum likelihood climate change for an energy balance system under the combined influence of greenhouse effect and α-stable Lévy motions. Additionally, there are also some researchers using the Lévy motion to characterize the random fluctuations emerged in neural systems [28], gene networks [6], epidemic model [21], and the Earth systems [2,20,33,34,37].…”
Section: Mathematics Subject Classification (2020) Msc 60g51 • Msc 60...mentioning
confidence: 99%
“…Subsequently, Zheng et al [41] developed a probabilistic framework to investigate the maximum likelihood climate change for an energy balance system under the combined influence of greenhouse effect and α-stable Lévy motions. Additionally, there are also some researchers using the Lévy motion to characterize the random fluctuations emerged in neural systems [31], gene networks [6], epidemic model [23], and the earth systems [2,22,36,37,40].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Greenland ice core measurement data, Ditlevsen [18] found that the temperature in that climate system could be modeled as stochastic differential equations with α-stable Lévy motion. Other researchers also used the non-Gaussian Lévy motion to characterize the random fluctuations emerged in neural systems [42], gene networks [8], and the Earth systems [3,58,60,55,53].…”
Section: Introductionmentioning
confidence: 99%